UPAYA PENCEGAHAN KEKERASAN SEKSUAL PADA ANAK USIA DINI BERBASIS ONLINE DI DESA WALUYA - Berliana Ayuningtyas; Lucky Purwantini; Tatang Iskandar (Universitas Islam 45 Bekasi, 2022)
The introduction of sex education in early childhood is still considered taboo andinappropriate by most parents. However, it is necessary to understand if there are thingsthat are important for us to teach children as early as possible in order to reduceunwanted actions such as sexual violence. The impact that will be felt and obtained byvictims of sexual violence will be very imprinted, both psychologically and physically. Theimportance of the role of parents in guiding and caring for children is one way to preventsexual violence in early childhood. The purpose of this activity is to provide information,discuss and train parents in order to increase public awareness in understanding theimportance of preventing sexual violence. This activity is carried out with 3 programactivities regarding the prevention of sexual violence, namely psychoeducation,socialization and training. Each activity takes place 3 (three) times in a communityservice program. Data collection was carried out before and after the activity took place.And at the end of the activity there is an evaluation conducted by the researcher.Researchers conduct online activities based on zoom meetings. Judging from the resultsin data collection, there are changes after the implementation of this program.